A social cognitive approach to burnout in elite athletes - Lemyre, P.-N.; Hall, H. K.; Roberts, G. C. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The purpose of this study was to investigate athlete burnout from a social-cognitive perspective by examining the relationship between social cognitive motivational variables at the start of a season and signs of burnout in elite athletes at the end of the season. Participants were 141 (F=60, M=81) elite winter sport athletes competing in Alpine skiing, Biathlon, Nordic Combined, Nordic skiing, and Speed skating. Participants completed a comprehensive motivation assessment package at the start of the season and a further burnout inventory at season's end. Results indicated that motivational dispositions, measures of the achievement climate, perceived ability and dimensions of perfectionism were associated with burnout in a conceptually consistent manner. Furthermore, the elite athletes could be grouped into two motivational profiles based on variables measured at the start of the season, one being adaptive and the other maladaptive. At season's end, the two different motivational profiles yielded distinctively different responses on an inventory assessing signs of burnout. The current findings strengthen the claim that burnout in elite athletes may not simply be "motivation gone awry" as Gould has suggested, but an inevitable consequence of exhibiting a maladaptive motivational profile.